MAPPING ECONOMY POTENCY AND REGIONAL INDEPENDENCY IN JAVA ISLAND DURING FISCAL DESENTRALIZATION ERA - Joko Tri Haryanto (Journal of Indonesian Applied Economics, 2017)
New decentralization regim implemented since 1 January 2001. Decentralization try to increase the improvement of public services. Based on the statictic data, Java recorded a major contributor to national GDP growth with many challenge on poverty and inequality. Using the share and growth analysis as well as quadrant method, this research tries to provide mapping economy potency and regional independency in Java. From the share analysis, still dominated by provincial government, which the biggest is DKI Jakarta Province. From the smallest share, Gunung Kidul Regency is the weakest independency. Based on growth analysis, Jepara Regency, Tangerang, Ngawi, Mojokerto and Tangsel City became the largest. From the quadrant method, 15 regions are in quadrant I, about 19 other areas are in quadrant II and 37 areas are in quadrant III. And largest part of the Java could classify in quadrant IV. According on these findings, central government must producing several policy to speed up the development regions particularly on all regional in quadrant IV.